Estudo do polimorfismo e modelagem molecular do gene TAS1R3 de indivíduos autistas - Gonçalves, Samille Oliveira (2019)
Autism is a rare and serious psychiatric disorder characterized by imbalanced intellectual development, which impairs the ability to socialize, and in some cases motor coordination. For the diagnosis of Autism Spectrum Disorder (ASD), the main characteristics observed are behavioral, where social interaction, communication (verbal and nonverbal), interests, repetitive and stereotyped behavior patterns, sensory and perceptual processing are observed. Some authors still report on food selectivity, which is very common in individuals diagnosed with ASD, where they associate food selectivity with sensory dysfunction. The TAS1R2 and TAS1R3 genes encode G-protein receptors, and are associated with sweet taste detection, and there are some studies that suggest that these genes also have the action of glucose sensors in nutrient-sensitive brain regions. TAS1R2 and TAS1R3 are located both in the tongue, acting as receptor of sweet taste, as well as in regions of the hypothalamus, where their function is not yet known in detail. In this perspective, this work verified polymorphisms, in the coding region of the active sites of the TAS1R3 protein, from genetic sequences obtained from autistic individuals. For this, methods of extraction, amplification, DNA sequencing, and homology molecular modeling were performed. We identified 28 different polymorphisms, with 4 mutations presenting conservation pattern among the samples. In the docking performed with the mutant proteins and the lactisole molecule, it was observed that there was no binding of this substance to the mutant proteins, suggesting that such mutations cause some change in the conformation structure of the mutant protein that interferes with the binding of the lactisole to it.